Acute and Sub-Acute Toxicity Evaluation of the Crude Methanolic Extract of Justicia schimperiana Leaf in Wistar Albino Rats - Jegnie M; Abula T; Woldekidan S; Chalchisa D; Asmare Z; Afework M (Dove Medical Press, 2023)
Mihretu Jegnie,1 Teferra Abula,2 Samuel Woldekidan,3 Dinkenesh Chalchisa,4 Zemen Asmare,5 Mekbeb Afework1 1Department of Anatomy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pharmacology, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Traditional and Modern Drug Research Directorate, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 4National Reference Laboratory for Immunohematology, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 5Department of Pathology, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Mihretu Jegnie, Addis Ababa University, P.O. Box 9086, Addis Ababa, Ethiopia, Tel +251 984 079 816, Email mihretuj@gmail.comPurpose: This study evaluates the acute and sub-acute toxicity of 80% methanolic extracts of the leaves of Justicia schimperiana in Wistar albino rat models.Methods: Dried powdered leaves of Justicia schimperiana were macerated in 80% methanol. The experiment was conducted in accordance with the Organization for Economic Co-operation and Development guideline 423 for acute and 407 for sub-acute toxicity testing. A single dose of 5000 mg/kg extract was orally administered to three female rats for the acute toxicity study. The plant extract was administered orally for 28 days in daily dosages of 250, 500, and 1000 mg/kg for the sub-acute study. Animals in a control group were given distilled water. A total of 40 rats (5 rats/group/sex) were used for the sub-acute toxicity testing. Daily food intake and weekly body weight measurements were done. The rats were sacrificed at the end of the 28-day treatment period for hematological, biochemical, and histopathological tests. One-way analysis of variance and Kruskal-Wallis tests were employed for the analysis.Results: The single-dose oral administration of the plant resulted in no deaths or serious morbidity. The median lethal dose was > 5000 mg/kg. The 28-day oral treatment of the plant extract had no significant effect on general behavior, food intake, organ weight, biochemical parameters, or the majority of the hematological markers, with the exception of the decrease in hemoglobin and hematocrit in the 1000 mg/kg extract-treated groups compared to the controls. Both sexes experienced significant weight increases at all dosage levels. With the exception of minor alterations in a few of the organs, no significant histological change was identified.Conclusion: It is concluded that the single-dose and repeated-dose 28-day oral administration of the methanolic leaf extract of Justicia schimperiana is relatively safe.Keywords: acute toxicity, sub-acute toxicity, Justicia schimperiana, rats, crude extract